Altman Z-Score and Zmijewski X-Score Models on Performance to Assess the Bankruptcy Risk of Mining Companies on IDX Indonesia 2018-2022 - Nerotumilena, Tresya; Winarna, Jaka (Universitas Muhammadiyah Yogyakarta, 2024)
Financial Distress Analysis is a method used to assess the financial condition of a company. This information is crucial for the company and stakeholders in the decision-making process. This research aims to project the potential financial distress of mining companies listed on the Indonesia Stock Exchange during the 2018-2022 period, using the Altman Z-Score and Zmijewski X-Score methods on financial performance. The research applied quantitative methods, with a descriptive and a different test assessment. Data analysis was carried out using the calculation of Altman Z-Score and Zmijewski X-Score using SPSS version 27. The results showed that over five years, out of 31 mining companies, the X-Score model had a significant value of 0.00 < 0.05 on performance, indicating that this method is good for use in mining companies. In conclusion, investors are advised to consider these findings when making investment decisions in the mining sector experiencing financial distress.